Are Proposed African Monetary Unions Optimal Currency Areas? Real and Monetary Policy Convergence Analysis - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose A spectre is hunting embryonic African monetary zones: the EMU crisis. This paper assesses real and monetary policy convergence within the proposed WAM and EAM zones. The introduction of common currencies in West and East Africa is facing stiff challenges in the timing of monetary convergence, the imperative of bankers to apply common modeling and forecasting methods of monetary policy transmission, as well as the requirements of common structural and institutional characteristics among candidate states. Design/methodology/approach In the analysis, monetary policy targets inflation and financial dynamics of depth, efficiency, activity and size while real sector policy targets economic performance in terms of GDP growth at macro and micro levels. Findings Findings suggest overwhelming lack of convergence: (1) initial conditions for financial development are different across countries; (2) fundamental characteristics as common monetary policy initiatives and IMF backed financial reform programs are implemented differently across countries; (3) there is remarkable evidence of cross-country variations in structural characteristics of macroeconomic performance; (4) institutional cross-country differences could also be responsible for the deficiency in convergence within the potential monetary zones. Practical implications As a policy implication, heterogeneous structural and institutional characteristics across countries are giving rise to different levels and patterns of financial intermediary development. Thus member states should work towards harmonizing cross-country differences in structural and institutional characteristics that hamper the effectiveness of convergence in monetary and real policies. Originality/value It is one of the few attempts to investigate the issue of convergence within the proposed WAM and EAM unions.
Keywords: F15; F36; F42; O55; P52; 330; Currency Area; Convergence; Policy Coordination; Africa